Some Refinements of Inequalities for Circular Functions - Zhengjie Sun; Ling Zhu (Journal of Applied Mathematics)
We give new lower bound and upper bound for Papenfuss-Bach inequality and improve Ruehr-Shafer inequality by providing a new lower bound.